CONTEXT AWARE MOBILE COMPUTING AS A CHALLENGE FOR DEVELOPERS AND SOFTWARE ENGINEERS:A REVIEW - Tahir, Rabail (European Scientific Journal, ESJ, 2014)
The trend of mobile computing has entered the society like rapidly flowing water. Almost every person wherever he is present, is getting benefits from it while working, studying, traveling or even for enjoyment. Due to this great demand of mobile computing there are some challenges such as context-awareness for the developers and the software engineers who are greatly concerned with the satisfaction and ease of their customers. The context aware mobile computing has gained an increasing recognition and is one of the emerging technologies for the mobile devices of next generation. This is a review paper in which we have generally discussed some of the issues of mobile computing with respect to software engineering and specifically we have reviewed some issues and problems of context aware mobile computing for developers as well as software engineers.